In Vivo Antihypercholesterolemic Potential of Swietenia mahagoni Leaf Extract - Yelaware Puttaswamy, Naveen (Cholesterol, 2016)
The present investigation aims to evaluate antihypercholesterolemic potential of Swietenia mahagoni leaf aqueous extract (MAE) in diet-induced hypercholesterolemic rat model. In the study, Wistar albino rats (170–220 g) were segregated into 5 groups; all the groups except normal control group were given high fat diet to induce hypercholesterolemia. After induction of cholesterolemia, normal control and positive control groups were treated with saline, statin group was treated with atorvastatin, and remaining two groups received MAE in two doses (250 and 500 mg kg(−1) BW) for a treatment period of one month. After the treatment period, weight of rats was recorded and they were anesthetized and decapitated. Blood samples were taken and triglycerides, total cholesterol, LDL-C, HDL-C, malondialdehyde (MDA), and urea were determined. Liver and kidney were taken for the estimation of lipid peroxides. The positive control group showed higher values of triglycerides (109 ± 5.1 mg/dL), total cholesterol (134 ± 4.6 mg/dL), LDL-C (44 ± 1.2 mg/dL), MDA, and bile acid content when compared to a normal control group (triglycerides (89 ± 3.2 mg/dL), total cholesterol (72 ± 3.4 mg/dL), and LDL-C (28 ± 1.2 mg/dL)). Treatment with MAE decreased the cholesterol levels, HDL-C, ALT, AST, and bilirubin levels and the effect was dependent on the dose. The results of this study indicated that MAE possesses hypolipidemic potential and thus could be useful in the treatment of hypercholesterolemic condition.